Refusal Strategies Among Sundanese Students: An Analysis of Gender and Power Relation - Rahmatillah Solihah (Universitas Pendidikan Indonesia (UPI), 2019)
This study aims to investigate the contribution of power relation to the realization of refusal strategies done by Sundanese male and female students. This study employs a descriptive qualitative approach. The data used in the present study were gathered from a Discourse Completion test (DCT) that was distributed to 4 male and 4 female respondents. The data were analyzed by using Takahashi and Beebe’s (1990) classifications of refusal. The findings show that there is no substantial difference in terms of the strategies employed by both genders. It is also found that power relation influences the realization of refusal. This finding suggests that when the respondents refuse someone who is more powerful, they tend to prioritize the emotional feeling of the requester. Meanwhile, when the respondents refuse someone who is more powerless, they tend to prioritize things by using their logic. Keywords: Refusal, genders, Sundanese, power relation